BALANCING TECHNOLOGY AND HUMAN VALUES: A LITERATURE REVIEW ON THE TRANSFORMATION OF TEACHERS' ROLES IN SHAPING A GENERATION WITH CHARACTER AND EMPATHY IN THE ERA OF SOCIETY 5.0 - Syamsu Qamar Badu; Novianty Djafri; Heldy Alam (International Journal of Teaching and Learning, 2025)
The development of technology in the era of Society 5.0 has brought significant changes in the world of education, demanding the transformation of the role of teachers from mere conveyors of knowledge to facilitators, models, and inspirers of character. This research aims to review the literature related to efforts to balance the use of technology with the cultivation of human values, especially character and empathy, in the education process. Through a qualitative literature study, it was found that teachers have a central role in guiding students to be not only digitally proficient, but also emotionally and socially mature. Effective strategies include integrating character values into technology-based learning, strengthening digital literacy and ethics, and collaboration between school, family and community. The results of the study confirm that technology should be positioned as a tool to strengthen character learning, not replace it, so that education in the era of Society 5.0 can produce a generation with character, empathy and readiness to face global challenges.